Gaseous Emissions from Wastewater Facilities. (1st October 2018) - Koh, Sock‐Hoon; Shaw, Andrew R.
Abstract : A review of the literature published in 2017 on topics relating to gaseous emissions from wastewater facilities is presented. This review is divided into the following sections: odorant emissions from wastewater treatment plants (WWTPs); greenhouse gas (GHG) emissions from WWTPs; gaseous emissions from wastewater collection systems; physiochemical odor/emissions control methods; biological odor/emissions control methods; odor/GHG characterization/monitoring/ modeling; and odor impacts/risk assessments.